Cortical bone porosity visualization using mercury porosimetry intrusion data - Cardoso,Antônio V. (2007)
Cortical bone porosity of bovine tibia samples has been investigated using the mercury intrusion porosimetry (MIP) technique. Cortical bone porosity range from 10 nm (caniculae) to 40 mm (Harvers canals), well in the measuring range region for the MIP technique. Samples from fresh bovine cortical bone were treated, dried and cut into ~ (3x1x1) cm pieces .The aim of the work was twofold: 1- To investigate bone porosity structure and direction quantitatively; 2- To obtain tri-dimensional scientific visualization (SV) images of cortical bone porosity. The MIP experiments associated with SV seem to be a good tool for studies of bone loss mechanisms, bone porosity distribution and bone growth phenomena.